Pengaruh Variabel Makroekonomi terhadap Pertumbuhan Sukuk Korporasi di Indonesia - Ivan Hannoeriadi Ardiansyah; Deni Lubis (AL-MUZARA'AH, 2017)
The development of the Islamic financial industry in Indonesia has increased from year to year. This is made possible due to the emergence of varied investment instruments, and corporate sukuk is one good example. Emergence corporate sukuk is expected encourage growth of the national economy. The growth of a good national economy is reflected by good macroecomic variables conditions. Therefore, the government and Bank Indonesia need to maintain inflation stability, money supply, exchange rate and output so that Indonesia can become the largest market center of corporate sukuk issuance. This research aims to analyze the effect of macroeconomic variables towards the growth of corporate sukuk in Indonesia. This research used Ordinary Least Square (OLS) with monthly time series data from January 2013 to December 2015. The results of this research indicate that the money supply, industrial production index, and inflation variables has positive effect (significantly) on the growth of corporate sukuk while exchange rate, oil price, and mudaraba deposit profit-sharing variables have negative effect (significantly).